A spatial analysis of the JBA headquarters in Splinter Cell: Double Agent - Martin, Paul (Elsevier, 2014)
Three measures drawn from space syntax are proposed as means of describing game spaces with a view to a morphological critical analysis. These measures are: core integration and segregation, isovist area, and visibility/accessibility discrepancy (VAD). The measures are applied to the JBA headquarters levels in the stealth game Splinter Cell: Double Agent in order to evaluate the space in terms of the navigational challenges and affordances with which it presents the player and in terms of the rhythms of tension and relief inherent in its layout. It is demonstrated how these challenges and rhythms are married to the specific game tasks and events that each level contains.